2015
DOI: 10.1016/j.jweia.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a new two-dimensional wake model for wind turbine wakes

Abstract: a b s t r a c tA new two-dimensional (2D) wake model is developed and validated in this article to predict the velocity and turbulence distribution in the wake of a wind turbine. Based on the classical Jensen wake model, this model is further employing a cosine shape function to redistribute the spread of the wake deficit in the crosswind direction. Moreover, a variable wake decay rate is proposed to take into account both the ambient turbulence and the rotor generated turbulence, different from a constant wak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 19 publications
0
94
0
Order By: Relevance
“…Some more details of the AD modeling approach and cross comparisons can be found from our previous works [32][33][34]. To show the model accuracy, in Figure 10, some results from the current simulations using RANS turbulence model are compared with the LES results under same flow conditions [27,28]. On the modeling of wind turbine wake, many studies can be found [29][30][31].…”
Section: Wake Modeling Of a Wind Turbine Clustermentioning
confidence: 99%
“…Some more details of the AD modeling approach and cross comparisons can be found from our previous works [32][33][34]. To show the model accuracy, in Figure 10, some results from the current simulations using RANS turbulence model are compared with the LES results under same flow conditions [27,28]. On the modeling of wind turbine wake, many studies can be found [29][30][31].…”
Section: Wake Modeling Of a Wind Turbine Clustermentioning
confidence: 99%
“…The 2 MW V80 wind turbine blade is composed of NACA63-series airfoils between the blade tip and the mid-span, and the FFA W3-series airfoils are used between the mid-span towards the blade inboard part. To validate the aerodynamic accuracy, the results from the present simulations and from the reference LES [26,54] simulations are compared. The inflow wind speed is 5.33 m/s, and turbulence intensity is 9.4% which are selected for fair comparison with some LES results.…”
Section: Horns Rev I Wind Farm Casementioning
confidence: 99%
“…The Jensen model is simple but shows useful results in the far-wake area. It is included as the basic model in many commercial software applications, and many derivative wake models have been developed [7][8][9][10][11]. Frandsen et al [12] proposed a wake model for predicting the wind speed deficit in an offshore wind farm where wind turbines are equally spaced and arranged in a grid form.…”
Section: Introductionmentioning
confidence: 99%